Analisa gambar citra MRI otak dengan watershed dan ekstraksi fitur GLCM - Astika Wulansari; Aulia Tegar Rahman (JNANALOKA, 2022)
Brain tumor is an infection in the form of unwanted tissue and considered as malignant. Nevertheless, it is very difficult to distinguish brain tumor tissue from the rest of the brain. Early detection of tumors is crucial to save the patient’s life. Segmentation strategy is used to identify and parse brain tumor areas utilizing the Magnetic ResonanceImaging (MRI) images of the brain. This is an important breakthrough for the future. Magnetic Resonance Imaging is an extreme field in the image processing area due to the very high level of precision needed by the doctors to obtain precise recommendations about the infections to save the patients’ lives. MRI images can be used to provide information on the separation of brain tumor tissue. Segmentation of MRI images with median filtering and skull stripping preprocessing techniques, threshold grip with watershed obtained contrast results of 4.287, correlation 0.946, homogeneity 0.721, and energy 0.278.